No excuses! : the power of self-discipline - Tracy, Brian (New York : Vanguard Press, 2010)
No Excuses! shows you how you can achieve success in all three major areas of your life: The first, your personal goals: self-discipline can help you realize that you are responsible for your success and shows you how persistence. really does pay off., the second, Your business and money goals: self-discipline can make you a better leader and a better manager, help you close more sales and make more money, improve your time-management and problem- solving abilities, and make you more effective and successful at work. The third, your overall happiness: self-discipline can help you be happier, healthier, and more physically fit, and it can help you in your marriage and your relationships with your children and friends.
Keywords: Self-control.; Self-management (Psychology); Success; Success in business